2022
DOI: 10.53730/ijhs.v6ns4.10033
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate prolectin-M, a galectin-3 antagonist, blocks SARS-CoV-2 activity

Abstract: The SARS-COV-2 (severe acute respiratory syndrome coronavirus 2) virus binds to human lectins to gain entry into cells to replicate. Blocking the virus’s entry using a complex polysaccharide component of [a (1-6)- D-mannopyranose termed “ProLectin M” has an effect on viral replication as a therapeutic tool and a safe alternative to existing antiviral therapies. Little is known about how galectin-3 inhibits viral entry into cells and its impact on the course of viral infection. Here, we investigated the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Additionally, no major adverse effects or abnormalities in vital signs, haematological, or biochemical parameters were identified after 7 days of PL-M administration. Our findings were consistent with those of earlier in vitro and clinical studies [23,24].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Additionally, no major adverse effects or abnormalities in vital signs, haematological, or biochemical parameters were identified after 7 days of PL-M administration. Our findings were consistent with those of earlier in vitro and clinical studies [23,24].…”
Section: Discussionsupporting
confidence: 93%
“…In our previous pilot study on 10 patients with COVID-19 infection, we found that oral administration of PL-M (chewable tablets) increased PCR cycle threshold, indicating the elimination of SARS-CoV-2 as well as a reduction in viral load in patients [23]. Further in vitro studies on SARS-CoV-2-infected Vero cells, followed by NMR analysis, revealed that PL-M strongly binds to human Gal-3, resulting in a reduction in viral load in Vero cells [24]. In this study, we further share the results of a clinical trial on CODID-19 patients and an NMR experiment with the extracted spike proteins.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations